VALIDASI INSTRUMEN BURNOUT UNTUK GURU SEKOLAH DASAR - Lestari, Dinda; Respati, Resa; Muhammad Hamzah, Rifqy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher burnout has become an important concern in elementary education due to increasing workloads, administrative demands, and emotional involvement in teaching activities. Therefore, a valid and reliable instrument is needed to accurately measure burnout among elementary school teachers. This study aimed to examine the psychometric properties of the Maslach Burnout Inventory (MBI) for elementary school teachers using the Rasch Model approach. The research employed a quantitative method with a survey design using a questionnaire consisting of 22 items adapted from the MBI dimensions, namely Emotional Exhaustion, Depersonalization, and Personal Accomplishment. Data were collected from 42 elementary school teachers and analyzed using Winsteps software based on the Rasch Model. Instrument quality was evaluated through item validity and reliability analysis, including Person Reliability, Item Reliability, and Cronbach’s Alpha. The results showed that 18 out of 22 items met the validity criteria and were retained, while four items were excluded due to misfit statistics. Reliability analysis indicated that the instrument demonstrated satisfactory reliability and consistency in measuring teacher burnout. The findings suggest that the modified Maslach Burnout Inventory is a valid and reliable instrument for assessing burnout among elementary school teachers. This instrument can be utilized in educational research and practice to identify burnout levels and support teacher well-being and professional performance.